2020
DOI: 10.1186/s42238-020-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent priapism in the setting of cannabis use

Abstract: Priapism (persistent and painful erection of the penis) is a notable urological emergency, with over 90% of those remaining erect for 24 h losing sexual function. Drug-induced priapism is common in the adult population, with intracavernosal injectables for erectile dysfunction topping the list. A variety of illicit drugs associated with priapism have been described; however, we are not aware of any other case reports showing cannabis alone as the inciting factor. Here, we present a case of a healthy 32-year-ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…As well as was concordant with Dutta, et al who identified that the mean age of the respondents was 29.8 years ± 13.3 years (29) . This is inconsistent with Montgomery, et al who found that the studied patients with priapism a Mean±SD= 23.6±8.8 years and were not married (31) . Similarly, Menon, and Rahman, reported that mostly of the studied case aged of a 20 year (32) .…”
Section: Participant (B): the Studied Patientscontrasting
confidence: 65%
“…As well as was concordant with Dutta, et al who identified that the mean age of the respondents was 29.8 years ± 13.3 years (29) . This is inconsistent with Montgomery, et al who found that the studied patients with priapism a Mean±SD= 23.6±8.8 years and were not married (31) . Similarly, Menon, and Rahman, reported that mostly of the studied case aged of a 20 year (32) .…”
Section: Participant (B): the Studied Patientscontrasting
confidence: 65%
“…However, our patient’s condition did not fulfill priapism diagnostic criteria because the penis was cut off before the erection exceeded 4 hours. Sickle cell disease as a priapism risk factor is a rare disease in our patient population, and his blood investigations did not demonstrate anemia [ 17 ]. Although there are some previous case reports about cannabis use and priapism, the reported patients used cannabis combined with other substances.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cannabinoid use promoting dopaminergic pathway might play a role in penile erection [ 19 ]. Moreover, cannabinoids block the thoracolumbar sympathetic pathway, which could result in the penis being unable to detumescence and increasing the risk of priapism [ 17 , 21 ]. THC interacts with a cannabinoid type 1 (CB1) receptor in the central nervous system (CNS), peripheral nervous system, and vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations